2017
DOI: 10.3390/rs9010068
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Forest Dynamics in the Andean Amazon: The Applicability of Breakpoint Detection Methods Using Landsat Time-Series and Genetic Algorithms

Abstract: Abstract:The Andean Amazon is an endangered biodiversity hot spot but its forest dynamics are less studied than those of the Amazon lowland and forests from middle or high latitudes. This is because its landscape variability, complex topography and cloudy conditions constitute a challenging environment for any remote-sensing assessment. Breakpoint detection with Landsat time-series data is an established robust approach for monitoring forest dynamics around the globe but has not been properly evaluated for imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Implementation of the feature selection algorithms in the Google Colab platform, which are divided into the wrapper and filter methods, can recognize and eliminate unrelated and redundant features and reduce the model complexity. For instance, Stromann et al (2020) [29], Cai et al (2018) [68], and Pal and Foody (2010) [69] reported the promising potential of wrapper methods, such as GA [64,[70][71][72][73][74], for finding the most-probable solutions without exploring the entire search space [36].…”
Section: Feature Selection In Google Colab Platformmentioning
confidence: 99%
“…Implementation of the feature selection algorithms in the Google Colab platform, which are divided into the wrapper and filter methods, can recognize and eliminate unrelated and redundant features and reduce the model complexity. For instance, Stromann et al (2020) [29], Cai et al (2018) [68], and Pal and Foody (2010) [69] reported the promising potential of wrapper methods, such as GA [64,[70][71][72][73][74], for finding the most-probable solutions without exploring the entire search space [36].…”
Section: Feature Selection In Google Colab Platformmentioning
confidence: 99%
“…Trend analyses of multiyear satellite images allow the capture of gradual LDD processes [74], but they are not independent from constraining assumptions like linearity. Trend analyses were routinely employed for LDD assessment using coarse-and multi-temporal imagery [75].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, our multi-date classification implementation was demonstrated to be far less sensitive to data scarcity and atmospheric contamination than other approaches using automated time-series analysis algorithms (Santos et al, 2017).…”
Section: Performance Of Multi-date Classification In the Unwmentioning
confidence: 96%
“…This results in time series with poor signal-to-noise ratio, as useful information about forest status is weak and not significant to differentiate from random noise. This is a limitation for transferring these novel algorithms to datascarce regions, such as the Tropical Andes (Santos, Dubovyk, & Menz, 2017), as time series analyses require rather dense data stacks over time.…”
Section: Introductionmentioning
confidence: 99%